Reseñas - Carla Perugini; María José Flores Requejo; Giovanna Minardi; Assunta Polizzi; Antonella Russo; Stefano Prandel; Andrés Ortega Garrido (Cuadernos AISPI)
Liliana Bellone, Eva Perón, allieva di Nervo, Salerno/Milano, Oèdipus, 2014, 184 pp. ISBN 9788873411895